2020
DOI: 10.1108/srj-03-2020-0092
|View full text |Cite
|
Sign up to set email alerts
|

Responsible leadership an obstacle for turnover intention

Abstract: Purpose The purpose of this paper is to investigate the extent to which ethical climate mediates between responsible leadership and employee turnover intention. Design/methodology/approach This study used the deductive logic approach to develop hypotheses and analytical framework. Data were collected through convenience sampling technique from branch-level employees of the Bank of Punjab Pakistan working in Lahore, Gujranwala and Gujrat Region. Data were analyzed to test the hypotheses via descriptive analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 75 publications
2
22
0
4
Order By: Relevance
“…RL has direct effects on ethical climate [66] as well as previously mentioned indirect effects on micro-level variables through the mediation of ethical climate [89]. The relationship between these variables needs further investigation.…”
Section: Meso-levelmentioning
confidence: 81%
See 1 more Smart Citation
“…RL has direct effects on ethical climate [66] as well as previously mentioned indirect effects on micro-level variables through the mediation of ethical climate [89]. The relationship between these variables needs further investigation.…”
Section: Meso-levelmentioning
confidence: 81%
“…Across several studies, RL showed negative associations with turnover intentions [59,62,63,67,89] as well as turnover rates [59]. The number of unique studies on RL and turnover intentions in addition to turnover rates from a large scale study (n = 4352) [59] gives considerable evidence of the relationship.…”
Section: Micro-levelmentioning
confidence: 96%
“…In Asian context, specific research investigates RL's effect on micro, meso and macro-level outcomes like unethical pro-organizational behaviour, talent retention, organizational citizenship behaviour, environmental performance, job performance and pandemic management (Yasin et al, 2020;Javed et al, 2020a;Afsar et al, 2020;Zhao and Zhou, 2019;Haque et al, 2019aHaque et al, , 2019bHan et al, 2019;Mehta et al, 2020;Lin et al, 2020). While exploring the Western developed notion of RL in the Asian context, Koh et al (2018) observed that Asian leaders possessed values and traits accordant with the Western concept of RL.…”
Section: Peeking Through the Asian Context Of Pakistanmentioning
confidence: 99%
“…If a company's employee-oriented social responsibility behavior is based on the Global Sullivan Principles, we can reasonably infer that there will be higher employee satisfaction. According to previous studies, a company's engagement in CSR activities changes the employees' perceptions of the company [30]. Since employee satisfaction is more difficult to observe and quantify, the data are limited.…”
Section: Csr and Employee Turnovermentioning
confidence: 99%
“…Lee, Park, and Lee [68] conducted a study on how employees perceive CSR-related activities conducted by their employers, and their findings indicate that CSR behavior affects employees' perceptions of CSR, and in turn enhances employees' reliance on their companies and their performance. Yasin, Namoco, Jauhar, Rahim, and Zia [30] investigated whether the ethical aspects of corporate leadership reduce employees' intention to leave the company and found that responsible leadership is positively correlated with the internal ethical climate within the company, which is negatively correlated with the employee turnover of the company.…”
Section: Research Hypothesismentioning
confidence: 99%